Superficial temporal artery pressure monitoring as an adjunct to regional cerebral oxygen saturation during transcarotid transcatheter aortic valve replacement: a case report - Naoki Awaya; Satoshi Jujo; Hidehiko Okuma; Yuji Kato; Kenichi Ueda (JA Clinical Reports, 2026)
Abstract Background Transcarotid transcatheter aortic valve replacement (TC-TAVR) requires common carotid artery (CCA) clamping, necessitating cerebral perfusion monitoring. Regional cerebral oxygen saturation (rSO 2 ) is widely used but limited by extracranial contamination. Superficial temporal artery (STA) pressure monitoring may reflect collateral perfusion pressure distal to the clamp because of ipsilateral internal carotid artery (ICA)–STA continuity during CCA clamping. Case presentation An 80-year-old man with severe aortic stenosis underwent TC-TAVR via the left CCA. Under ultrasound guidance, we placed a 24-gauge catheter in the left STA to monitor collateral perfusion pressure during CCA clamping. STA mean arterial pressure (MAP) decreased from 81 to 35 mmHg upon CCA clamping and was targeted at ≥ 40 mmHg with norepinephrine, except during rapid pacing for valve deployment. He was discharged on postoperative day 5 uneventfully. Conclusions STA pressure may provide supplementary collateral perfusion information to rSO 2 during CCA clamping, and ultrasound-guided STA cannulation was feasible.